Les races bovines de l'Adamaoua (Cameroun) - Lhoste, Philippe (1971)
The various cattle breeds of the Adamawa were described. Discussions and data on animal performance; introduction of exotic breeds and determination of breeding potential of different breeds in the region, specially Adamawa cattle, Red Bororo cattle and Wakwa cattle included.